Rates of palaeoecological change can inform ecosystem restoration - W. Finsinger; C. Bigler; C. Schwörer; W. Tinner (Biogeosciences, 2024)
Accelerations of ecosystem transformation raise concerns, to the extent that high rates of ecological change may be regarded amongst the most important ongoing imbalances in the Earth system. Here, we used high-resolution pollen and diatom assemblages and associated ecological indicators (the sum of tree and shrub pollen and diatom-inferred total phosphorus concentrations as proxies for tree cover and lake-water eutrophication, respectively) spanning the past 150 years to emphasize that rate-of-change records based on compositional data may document transformations having substantially different causes and outcomes. To characterize rates of change also in terms of other key ecosystem features, we quantified for both ecological indicators: (i) the percentage of change per unit time, (ii) the percentage of change relative to a reference level, and (iii) the rate of percentage change per unit time relative to a reference period, taking into account the irregular spacing of palaeoecological data. These measures document how quickly specific facets of nature changed, their trajectory, as well as their status in terms of palaeoecological indicators. Ultimately, some past accelerations of community transformation may document the potential of ecosystems to rapidly recover important ecological attributes and functions. In this context, insights from palaeoecological records may be useful to accelerate ecosystem restoration.